The diagnostic and therapeutic potential of exosomal proteins in breast cancer - A. A. Shefer; Ya. A. Frik; S. N. Tamkovich (Успехи молекулярной онкологии, 2023)
Exosomes are membrane vesicles 30–150 nm in size released by cells upon fusion of multivesicular bodies with the plasma membrane. A distinctive feature of these vesicles is the presence of the surface tetraspanins CD9, CD63, and CD81. The Rab family of small GTPases, including Rab27A and Rab27B, controls various steps in exosome release, including transport of multivesicular bodies and fusion of the multivesicular body to the plasma membrane. It is commonly accepted to date that exosomes are the main carriers of information between cells under physiological conditions, such as mammary development and lactation, and under pathological conditions, such as breast cancer. This review considers the peculiarities of exosome formation, secretion and transport, their composition and role in normal and breast cancer, as well as the prospects for using these vesicles to develop early non-invasive diagnostics and improve the effectiveness of anti-tumor therapy.